ALOX5 inhibition protects against dopaminergic neurons undergoing ferroptosis - Kun Li; Meng Wang; Zi-Han Huang; Min Wang; Wan-Yang Sun; Hiroshi Kurihara; Rui-Ting Huang; Rong Wang; Feng Huang; Lei Liang; Yi-Fang Li; Wen-Jun Duan; et al. (Pharmacological Research, 2023)
Oxidative disruption of dopaminergic neurons is regarded as a crucial pathogenesis in Parkinson's disease (PD), eventually causing neurodegenerative progression. (-)-Clausenamide (Clau) is an alkaloid isolated from plant Clausena lansium (Lour.), which is well-known as a scavenger of lipid peroxide products and exhibiting neuroprotective activities both in vivo and in vitro, yet with the in-depth molecular mechanism unrevealed. In this study, we evaluated the protective effects and mechanisms of Clau on dopaminergic neuron. Our results showed that Clau directly interacted with the Ser663 of ALOX5, the PKCα-phosphorylation site, and thus prevented the nuclear translocation of ALOX5, which was essential for catalyzing the production of toxic lipids 5-HETE. LC-MS/MS-based phospholipidomics analysis demonstrated that the oxidized membrane lipids were involved in triggering ferroptotic death in dopaminergic neurons. Furthermore, the inhibition of ALOX5 was found to significantly improving behavioral defects in PD mouse model, which was confirmed associated with the effects of attenuating the accumulation of lipid peroxides and neuronal damages. Collectively, our findings provide an attractive strategy for PD therapy by targeting ALOX5 and preventing ferroptosis in dopaminergic neurons.